2019
DOI: 10.21608/jpp.2019.36269
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Ineffective of some Resistance Genes to Wheat Leaf, Stem and Yellow Rust Diseases in Egypt

Abstract: One hundred and five wheat genotypes; 38 wheat leaf rust monogenic lines, 46 stem rust monogenic lines and 17 yellow rust monogenic lines, thee commercial wheat cultivars; Sakha 95, Misr 3 and Gemmeiza 11 and the highly susceptible variety Morocco were evaluated for their adult plant resistance and stability of resistance to rust diseases under different field conditions at Sadat City and Elbostan for three successive growing seasons i.. Depending on the obtained results, differences between environments, geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It is usually occurs at a higher level of severity on the late sowing dates than the early ones, when the environmental conditions were suitable for rust incidence and development [32]. It has been recently became a macro cyclic rust disease, [27], causing a serious economic loss in the highly susceptible wheat cultivars, [6,16,18,48]. Stripe rust was a dominant disease in Central Asian countries, since the late 1990s and early 2000s, where yield losses were reached to 20% and 40% in 1999 and 2000 [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually occurs at a higher level of severity on the late sowing dates than the early ones, when the environmental conditions were suitable for rust incidence and development [32]. It has been recently became a macro cyclic rust disease, [27], causing a serious economic loss in the highly susceptible wheat cultivars, [6,16,18,48]. Stripe rust was a dominant disease in Central Asian countries, since the late 1990s and early 2000s, where yield losses were reached to 20% and 40% in 1999 and 2000 [30].…”
Section: Introductionmentioning
confidence: 99%
“…These monogenic lines were stable with some races and less stable with other races according the used temperature regimes. Moreover, El-Orabey et al (2019b) found that the Lr 22 a, Lr 14b and Lr 28 were stable in efficacy at adult plant stage during the three growing seasons; 2017/2018, 2018/2019 and 2019/2020. Using different races of P. triticina in this study also explain why our data display the two monogenic lines; Lr 16 and Lr 17 were temperature sensitive while Brwoder (1980) grouped them as insensitive.…”
Section: Discussionmentioning
confidence: 89%
“…Of them, Sr2 has been successfully deployed in many breeding programs around the world like Australia, India, CIMMYT, and China due to its high yield and resistance to stem rust (McIntosh 1995;Malik et al, 2013, Bhavani et al, 2014Xu et al, 2017). In Egypt, Sr2 has been evaluated under field condition and provide high resistance to stem rust (El shamy et al, 2019;Shahin et al, 2020;Elkot et al, 2016;El-Orabey et al, 2019). Also, Singh et al (2006) reported that both Sonalika and Pavon 76 (Sr2) were resistant during field assessments in 2004 and 2005 in Kenya with a maximum disease score of 15MS.…”
Section: Discussionmentioning
confidence: 99%